A critical reflection on the formalisation of communal land rights in Namibia : why local contexts matter for bridging the dichotomies of tenure rights - Matthaei, Elke Astrid (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University 2018.